BS HD 60269-3. Low-voltage fuses. Part 3. Supplementary requirements for fuses for use by unskilled persons (fuses mainly for household or similar applications). Examples of standardized systems of fuses A to F (8th October 2021) - British Standards Institution,
No abstract available